2018
DOI: 10.1016/j.jsps.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The possible mechanisms of protocatechuic acid-induced central analgesia

Abstract: It is aimed to investigate the central antinociceptive effect of protocatechuic acid and the involvement of stimulation of opioidergic, serotonin 5-HT, α2-adrenergic and muscarinic receptors in protocatechuic acid-induced central analgesia in mice. Time-dependent antinociceptive effects of protocatechuic acid at the oral doses of 75, 150 and 300 mg/kg were tested in hot-plate (integrated supraspinal response) and tail-immersion (spinal reflex) tests in mice. To investigate the mechanisms of action; the mice ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…As part of an attempt to establish the antinociceptive potential of D. linearis and to promote the use of medicinal plants as pain-relieving agent, MEDL was also subjected to phytoconstituents analyses using the UHPLC-ESI-HRMS and GC-MS methods to determine the presence of polyphenolics or any volatile bioactive compounds with potential antinociceptive activity, respectively. The UHPLC-ESI-HRMS analysis of MEDL leads to identification of approximately 30 polyphenolic compounds of which several of them, such as gallic acid [60,61], ferulic acid [62], protocatechuic acid [63], caffeic acid [64,65], p-coumaric acid [66], rutin [67,68], isoquercitrin [69], astragalin [70], catechin [71], quercetin [72,73], apigenin [74] and kaempferol [75], have been reported to show antinociceptive activity. These reports also revealed that: (i) gallic acid was reported to show low antinociceptive activity against the acetic acid-induced nociception [60] while its derivative (gallic acid ethyl ester) was reported to attenuate bradykininand formalin-induced nociception [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of an attempt to establish the antinociceptive potential of D. linearis and to promote the use of medicinal plants as pain-relieving agent, MEDL was also subjected to phytoconstituents analyses using the UHPLC-ESI-HRMS and GC-MS methods to determine the presence of polyphenolics or any volatile bioactive compounds with potential antinociceptive activity, respectively. The UHPLC-ESI-HRMS analysis of MEDL leads to identification of approximately 30 polyphenolic compounds of which several of them, such as gallic acid [60,61], ferulic acid [62], protocatechuic acid [63], caffeic acid [64,65], p-coumaric acid [66], rutin [67,68], isoquercitrin [69], astragalin [70], catechin [71], quercetin [72,73], apigenin [74] and kaempferol [75], have been reported to show antinociceptive activity. These reports also revealed that: (i) gallic acid was reported to show low antinociceptive activity against the acetic acid-induced nociception [60] while its derivative (gallic acid ethyl ester) was reported to attenuate bradykininand formalin-induced nociception [61].…”
Section: Discussionmentioning
confidence: 99%
“…These reports also revealed that: (i) gallic acid was reported to show low antinociceptive activity against the acetic acid-induced nociception [60] while its derivative (gallic acid ethyl ester) was reported to attenuate bradykininand formalin-induced nociception [61]. In addition, gallic acid ethyl ester was ineffective in the hot-plate test and demonstrated partly the opioid/NO-independent action; (ii) ferulic acid exerts an opioid-mediated antinociceptive activity when assessed using the hot plate test [62]; (iii) protocatechuic acid also exerts an opioid-mediated antinociceptive activity when assessed using the hot plate test [63]; (iv) caffeic acid demonstrated the antinociceptive activity against the abdominal constriction test and the late phase of the formalin-induced nociception, but not the hot plate test [64] whereas the dodecyl ester derivative of caffeic acid were reported to produce antinociceptive activity against the abdominal constriction test as well as the formalin-, capsaicin-and glutamate-induced nociceptive model [65]; (v) rutin exerts antinociceptive activity when assessed using the abdominal constriction test and the formalin-induced nociception, respectively [66,67] with Hernandez-Leon et al [67] also showed that rutin produces an opioid-mediated antinociceptive activity only in the late phase of the formalin-induced test; (vi) isoquercitrin exhibits antinociceptive activity against the abdominal constriction and formalin tests [68]; (vii) astragalin demonstrates an opioid-mediated antinociceptive activity when assessed using the hot plate test and the formalin-induced nociception [69]; (viii) catechin produces antinociceptive activity against the abdominal constriction, hot plate and formalin-induced paw licking tests with an opioid-independent activity shown using the hot plate test [70]; (ix) quercetin was earlier reported to show an opioid-mediated antinociceptive activity when assessed using the hot plate test [71] while later study demonstrates that quercetin produces antinociceptive activity against the abdominal constriction test, as well as the formalin-, capsaicin-and glutamate-induced nociceptive tests that involves an interaction with l-arginine/NO pathway [72]; (x) apigenin was found to show antinociceptive activity against the abdominal constriction, hot plate and formalin-induced paw licking tests with the centrally-mediated opioid activity proven using the hot plate test [73]; and (xi) kaempferol derivatives (i.e., kaempferol 3-O-rutinoside, kaempferol 3-O-glucoside and kaempferol-3,7-di-O-α-l-rhamnopyranoside) was reported to exert antinociceptive activity against the abdominal constriction and formalin-induced paw licking tests [74,75]. In addition, Ali et al [75] also...…”
Section: Discussionmentioning
confidence: 99%
“…The later formula was applied in order to calculate maximal possible effect (MPE%) according to the results obtained by the hot-plate and tail-flick assays [22,23]. The maximal possible effect percentage ascertained by the response latency against thermal stimulus: MPE% = [{(Post-drug latency)−(Pre-drug latency)} / {(Cut-off time)−(Pre-drug latency)}] X100…”
Section: Tail-flick Testmentioning
confidence: 99%
“…The 20s were chosen as cut-off time in order to minimize hind paw damage. Finally, the mice behavior was recorded before treatment and after treatment [44].…”
Section: Hot-plate Testmentioning
confidence: 99%